2010
DOI: 10.3109/10884601003777638
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Quit Smoking Among Veterans Diagnosed with Psychiatric and Substance Abuse Disorders

Abstract: While smoking, psychiatric and substance abuse disorders are high among veterans, there is considerable controversy over providing smoking cessation interventions to those suffering with psychiatric and substance abuse disorders. The objective of this study was to determine motivation to quit smoking among veterans experiencing psychiatric and substance abuse disorders. A convenience sample of patients recruited at a primarily psychiatric Veterans Affairs hospital completed a self-administered survey (N = 146)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
(61 reference statements)
0
6
0
1
Order By: Relevance
“…However, those admitted for psychiatric/substance abuse tended to be less likely to quit. Research has shown that those with psychiatric and substance abuse disorders are interested in quitting [ 18 ], although quitting can be difficult among this population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, those admitted for psychiatric/substance abuse tended to be less likely to quit. Research has shown that those with psychiatric and substance abuse disorders are interested in quitting [ 18 ], although quitting can be difficult among this population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…선행연구에 따르면 흡연 정신질환자들도 일반인과 동일 하게 금연을 위해 도움 받기를 원하고 [10], 실제로 금연치 료나 중재가 정신질환자의 금연에 도움을 줄 수 있다고 보 고되었다 [11]. 다만 인지 및 사회적 기능, 정서적 문제를 가진 조현병, 양극성 장애, 우울장애 등의 정신질환자가 성공적으로 금연을 실천하도록 하기 위해서는 일반인 대 상으로 개발된 금연 프로그램은 효과적이지 않고 이들의 특성을 반영한 금연 프로그램이 제공될 필요가 있다 [8,12].…”
unclassified
“…Targeted, cessation initiatives are needed in this population, especially in the inpatient setting, which when compared to outpatient programs, tend to enroll more smokers and result in higher cessation rates (Duffy et al, 2008;Rigotti et al, 2007). Veteran smokers with mental illness are motivated to quit and appear to benefit from exposure to evidence-based tobacco cessation treatments (Duffy, Essenmacher, Karvonen-Gutierrez, & Ewing, 2010;Solty et al, 2009;Williams & Ziedonis, 2004). Thus, the inpatient setting provides an excellent opportunity to provide cessation services to this at-risk population.…”
Section: Discussionmentioning
confidence: 96%
“…Integrating smoking cessation services into standard of care on inpatient psychiatric units has the potential to capture more smokers and result in higher cessation rates (Duffy et al, 2008;Hall & Prochaska, 2009;Rigotti et al, 2007). Coupled with the fact that the majority of studies have shown that Veterans with psychiatric conditions are motivated to quit smoking, yet many still do not receive smoking cessation services, failure to address tobacco use during the inpatient hospital stay is a large missed opportunity with this vulnerable population (Duffy, Essenmacher, Karvonen-Gutierrez, & Ewing, 2010;Solty, Crockfrod, White, & Currie, 2009;Williams & Ziedonis, 2004).…”
Section: Receipt Of Servicesmentioning
confidence: 97%
See 1 more Smart Citation